2021
DOI: 10.1136/bmjopen-2020-044829
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand tobacco smoke exposure among children under 5 years old: questionnaires versus cotinine biomarkers: a cohort study

Abstract: ObjectivesCotinine is the gold standard to estimate prevalence of secondhand tobacco smoke (SHS) exposure, and assay limit of detection (LOD) cut-points are typically used regardless of age. Our aim was to compare the concordance between mother-reported SHS exposure and serum cotinine categorising children as exposed with the assay LOD or age-specific cut-points.DesignData from the Health Outcomes and Measures of the Environment (HOME) Study, a prospective pregnancy and birth cohort.SettingHospital or particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…A low HPS assessed by the self-report does not necessarily mean less exposure to smoking in the home. Previous studies have revealed that SR does not reflect exposure at home fully 17,32 . Thirdhand smoke could happen in home without secondhand smoke, and homes are more vulnerable to long-term exposure to smoking materials, including thirdhand smoke, because people stay more at home than anywhere else 33 .…”
Section: Discussionmentioning
confidence: 92%
“…A low HPS assessed by the self-report does not necessarily mean less exposure to smoking in the home. Previous studies have revealed that SR does not reflect exposure at home fully 17,32 . Thirdhand smoke could happen in home without secondhand smoke, and homes are more vulnerable to long-term exposure to smoking materials, including thirdhand smoke, because people stay more at home than anywhere else 33 .…”
Section: Discussionmentioning
confidence: 92%
“…One study considered the possibility of misclassification due to the inadequacy of the cut-point [ 40 ]. A recent cohort study assessing SHS exposure among children younger than 5 years, observed that, compared to the assay LOD derived cut-point of 0.015 ng/ml, when using new age-specific cut-points, all of them higher than the mentioned assay threshold, concordance between maternal self-report and serum cotinine improved; actually, the percentage of children reclassified as SHS exposed with cotinine disminished in approximately fifty percentage points when using the age-specific cut-points obtained with ROC curves [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cotinine, the major metabolite of nicotine, is one of the most commonly used biomarkers for assessing recent SHS exposure because of its high specificity and sensitivity [4]. In the past decade, more than 40% of US children aged 3 to 11 years had serum cotinine levels consistent with exposure to SHS [5]; we previously showed a similar SHS exposure prevalence among children aged 1 to 4 years from the Health Outcomes and Measures of the Environment (HOME) Study cohort [6].…”
Section: Introductionmentioning
confidence: 94%